2020
DOI: 10.1097/sla.0000000000004412
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Conference Statement on the General Use of Near-infrared Fluorescence Imaging and Indocyanine Green Guided Surgery

Abstract: Background:In recent decades, the use of near-infrared light and fluorescence-guidance during open and laparoscopic surgery has exponentially expanded across various clinical settings. However, tremendous variability exists in how it is performed.Objective:In this first published survey of international experts on fluorescence-guided surgery, we sought to identify areas of consensus and nonconsensus across 4 areas of practice: fundamentals; patient selection/preparation; technical aspects; and effectiveness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 49 publications
(121 reference statements)
1
53
0
Order By: Relevance
“…In recent years, several strategies have been investigated aimed at intraoperatively visualizing the single-patient lymphatics' anatomy for surgical guidance. Indocyanine-green (ICG) is a fluorescent fluorophore that over the past decades has been tested and used across an ever-expanding range of clinical setting [15][16][17]. In particular, ICG, which after direct tissue injection migrates in lymphatics and lymph nodes providing an intraoperative map of the tumor-specific draining area [18], is emerging as the preferred modality for lymphatic mapping in colon and rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several strategies have been investigated aimed at intraoperatively visualizing the single-patient lymphatics' anatomy for surgical guidance. Indocyanine-green (ICG) is a fluorescent fluorophore that over the past decades has been tested and used across an ever-expanding range of clinical setting [15][16][17]. In particular, ICG, which after direct tissue injection migrates in lymphatics and lymph nodes providing an intraoperative map of the tumor-specific draining area [18], is emerging as the preferred modality for lymphatic mapping in colon and rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In several recent reviews on fluorescence-guided abdominal surgery, a lack of quantitative, unbiased data in the available literature and the need for further research into the specifics of its application were pointed out [ 24 , 30 , 31 , 32 ]. The authors of these reviews remarked that the reported approaches of vascular perfusion assessment with ICG do not take into account the accumulation of ICG over time.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical setting often needs different scale to accommodate various imaging application, such as tissue perfusion test and tumor margin assessment [ 12 , 13 , 68 ]. Fluorescence imaging at different scales hold great promise for solving many clinical problems [ 69 ].…”
Section: Discussionmentioning
confidence: 99%